Efforts to Increase Reading Interest in Adolescents 17-23 Years Old: (Literacy Habituation on Jalan Sukabumi in the City of Bandung) - Rara Pringgandinie, Desty; Abdul Muluk, Kiki; Andikarya, R. Oke (Annpublisher, 2025)
Increasing reading interest in adolescents aged 17-23 years is a significant challenge in improving literacy in society. This effort involves a literacy habituation strategy that focuses on developing consistent and engaging reading habits. The methods used include the introduction of popular books, book discussion programs, and the use of technology to facilitate access to digital literacy resources. The results of the study show that with the implementation of the right literacy habituation strategy, adolescents can increase their interest in reading and develop sustainable reading habits, while the methods used are literacy habituation and field research to gain a comprehensive understanding. The results of the study show that environmental, educational, and parental factors play an important role in shaping and increasing reading interest in adolescents.